Immune dysregulation may contribute to disease pathogenesis in spinal muscular atrophy mice - Deguise, Marc-Olivier (Hum Mol Genet, 2017)
Spinal muscular atrophy (SMA) has long been solely considered a neurodegenerative disorder. However, recent work has highlighted defects in many other cell types that could contribute to disease aetiology. Interestingly, the immune system has never been extensively studied in SMA. Defects in lymphoid organs could exacerbate disease progression by neuroinflammation or immunodeficiency. Smn depletion led to severe alterations in the thymus and spleen of two different mouse models of SMA. The spleen from Smn depleted mice was dramatically smaller at a very young age and its histological architecture was marked by mislocalization of immune cells in the Smn(2B/-) model mice. In comparison, the thymus was relatively spared in gross morphology but showed many histological alterations including cortex thinning in both mouse models at symptomatic ages. Thymocyte development was also impaired as evidenced by abnormal population frequencies in the Smn(2B/-) thymus. Cytokine profiling revealed major changes in different tissues of both mouse models. Consistent with our observations, we found that survival motor neuron (Smn) protein levels were relatively high in lymphoid organs compared to skeletal muscle and spinal cord during postnatal development in wild type mice. Genetic introduction of one copy of the human SMN2 transgene was enough to rescue splenic and thymic defects in Smn(2B/-) mice. Thus, Smn is required for the normal development of lymphoid organs, and altered immune function may contribute to SMA disease pathogenesis.